Reform of the public pension system in Germany - Kai A. Konrad; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
This paper studies the current crisis in the German pension system and discusses the various reform proposals.
Keywords: 330; Gesetzliche Rentenversicherung; Rentenreform; Generationenbeziehungen; Kapitaldeckungsverfahren; Deutschland